2013
DOI: 10.15557/jou.2013.0020
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of ultrasound in the diagnostics of Sjögren’s syndrome

Abstract: Sjögren's syndrome is an autoimmune exocrinopathy which manifests itself with dryness of the eyes and the oral cavity. These symptoms comprise a so-called sicca syndrome (xerostomia and xerophthalmia). Two forms of this disease may be distinguished: primary Sjögren's syndrome which affects salivary glands and secondary Sjögren's syndrome with other autoimmune diseases present such as rheumatoid arthritis, systemic lupus erythematosus or systemic scleroderma. The diagnosis is based on the classification criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
7
0
5
Order By: Relevance
“…It may be expected that the application of UHFUS to major SGs investigation may lead to an increase of the overall diagnostic accuracy in patient with pSS, particularly in the early phases. Indeed, the role of SGUS in the early diagnosis of pSS is still controversial (50). Although some authors stated that normal US findings in SGs have been observed in patients suffering from pSS for about 4.2 years (51), a recent study described the role of SGUS in the early diagnosis of pSS considering patients with symptoms duration inferior to 5 years (52).…”
Section: Sgs Uhfus In Ss: Current Conceptsmentioning
confidence: 99%
“…It may be expected that the application of UHFUS to major SGs investigation may lead to an increase of the overall diagnostic accuracy in patient with pSS, particularly in the early phases. Indeed, the role of SGUS in the early diagnosis of pSS is still controversial (50). Although some authors stated that normal US findings in SGs have been observed in patients suffering from pSS for about 4.2 years (51), a recent study described the role of SGUS in the early diagnosis of pSS considering patients with symptoms duration inferior to 5 years (52).…”
Section: Sgs Uhfus In Ss: Current Conceptsmentioning
confidence: 99%
“…To obvykle začíná unilaterálně, později však dojde i k postižení druhostranné slinné žlázy [28]. Při sonografickém zobrazení bývají v slinných žlázách nacházeny typické změny ve smyslu hypoechogenit [31,41]. Rychlé zvětšení slinné žlázy může být předzvěstí vývoje maligního B-lymfomu.…”
Section: Zduření Slinných žLázunclassified
“…(4) Additionally, the following examinations can be done: computed tomography, ultrasound scan, and MRI. (5) The most reliable methods recognized to detect typical changes in the glandular tissue during SS are salivary gland biopsy and sialograph. (6) However, performing a sialography is often impossible in patients with allergic reactions to the iodine medications and in cases of thyroid diseases, as the administration of the iodine-containing contrast agent is required to perform it.…”
Section: Introductionmentioning
confidence: 99%
“…This is shown on sonograms in the form of hypoechoic areas surrounded by a hyperechoic line or spot, resembling a reticulated image. (5) At the same time, this complex of symptoms can correspond either to the accumulation of the lymphoid cells or to the finefocal lymphomas and can be mistakenly interpreted. (8) The important data about structural changes of PSG and about the presence and distribution of the adipose tissue can be obtained with an MRI.…”
Section: Introductionmentioning
confidence: 99%